Action can amplify motion-induced illusory displacement - Caniard, Franck; Bülthoff, Heinrich H.; Thornton, Ian M. (Frontiers in Human Neuroscience, 2015)
Local motion is known to produce strong illusory displacement in the perceived position of globally static objects. For example, if a dot-cloud or grating drifts to the left within a stationary aperture, the perceived position of the whole aperture will also be shifted to the left. Previously, we used a simple tracking task to demonstrate that active control over the global position of an object did not eliminate this form of illusion. Here, we used a new iPad task to directly compare the magnitude of illusory displacement under active and passive conditions. In the active condition, participants guided a drifting Gabor patch along a virtual slalom course by using the tilt control of an iPad. The task was to position the patch so that it entered each gate at the direct center, and we used the left/right deviations from that point as our dependent measure. In the passive condition, participants watched playback of standardized trajectories along the same course. We systematically varied deviation from midpoint at gate entry, and participants made 2AFC left/right judgments. We fitted cumulative normal functions to individual distributions and extracted the PSE as our dependent measure. To our surprise, the magnitude of displacement was consistently larger under active than under passive conditions. Importantly, control conditions ruled out the possibility that such amplification results from lack of motor control or differences in global trajectories as performance estimates were equivalent in the two conditions in the absence of local motion. Our results suggest that the illusion penetrates multiple levels of the perception-action cycle, indicating that one important direction for the future of perceptual illusions may be to more fully explore their influence during active vision.